Kajian Empat Varietas Unggul Padi dengan Sistem Tanam Jarwo 2 : 1 di Lahan Rawa Lebak Desa Sukarame Kabupaten Ogan Komering Ilir, Sumatera Selatan - Suparwoto, Suparwoto; Harnisah, Harnisah; Waluyo, Waluyo (Seminar Nasional Lahan Suboptimal, 2019)
Suparwoto S, Harnisah H, Waluyo W. 2019. Assesment four varieties superior rice with plant system jarwo 2:1 at Sukarame village, Ogan Komering Ilir District, South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 53-61.  Palembang: Unsri Press.One of the technologies that is environmentally friendly, safe and low-cost includes high-yielding varieties that can boost the increase in rice production. This activity was carried out in Sukarame Village, Tanjung Lubuk Subdistrict, Ogan Komering Ilir Regency, South Sumatra, in April-August 2018. The aim was to obtain high-yielding varieties that could adapt and produce high using planting system jarwo 2:1 in swampy lands. Materials needed include: Inpari 30, Inpari 33, Inpari 43 and Inpari 30 (SS class), urea, SP-36, KCl, pesticides, herbicides and tarps. In addition, the tools needed include: hand tractor, meter, scales, machetes, hoes, sprayers. The varieties studied were 4 varieties consisting of Inpari 30, Inpari 33, Inpari 43 and Inpara 8. The method used was direct observation in the field, the study area was 3 hectares. Fertilizers used are 150 kg Urea, 100 kg SP-36 and 100 kg KCl/ha. Fertilization is done twice, namely at the age of 1 week after planting with a dose of 75 kg urea, 100 kg SP-36 and 100 kg KCl/ha and at 4 weeks after planting  at a dose of 75 kg urea/ha. The planting system used is Legowo 2: 1 (50 cm x 25 cm x 12.5 cm). Data collected included: crop height at harvest, number of productive tillers/clumps, panicle length, number of grains per panicle, number of filled grains per panicle, and production of conversion grain per hectare. The method used is direct observation in the field of superior varieties exhibited. The data obtained were arranged in tabulation and analyzed by statistical tests, namely the test of the mean value (test-t). Data analysis was carried out with the SPSS 11 program. The results showed that Inpari 30, Inpari 33, Inpari 43 and Inpara 8 were grown with jajar legowo 2: 1 planting system that could adapt to swampy lands with production ranging from 4.3 to 5.5 tons GKP/ha, where the production of Inpara 8 is higher than other varieties which is 5.5 tons GKP/ha, followed by Inpari 43 which is 5.3 tons GKP / ha. Keywords: assesment, jarwo 2:1, swampy lands, superior varieties rice